The integrative genomic and functional immunological analyses of colorectal cancer initiating cells to modulate stemness properties and the susceptibility to immune responses - Issam Tout; Salim Bougarn; Mohammed Toufiq; Neha Gopinath; Ola Hussein; Abbirami Sathappan; Evonne Chin-Smith; Fazulur Rehaman; Rebecca Mathew; Lisa Mathew; Kun Wang; Li Liu; et al. (Journal of Translational Medicine)
Abstract Background Colorectal cancer (CRC) initiating cells (CICs) possess self-renewal capabilities and are pivotal in tumor recurrence and resistance to conventional therapies, including immunotherapy. The mechanisms underlying their interaction with immune cells remain unclear. Methods We conducted a multi-omics analysis—encompassing DNA methylation, total RNA sequencing, and microRNAs (miRNAs; N = 800) profiling on primary CICs and differentiated tumor cell lines, including autologous pairs. Functional immunological assays were performed to assess the impact of miRNA modulation. Results CICs exhibited distinct methylation patterns, transcriptomic profiles, and miRNA expressions compared to differentiated tumor cells (p < 0.05 or 0.01). Notably, miRNA-15a and -196a were implicated in regulating tumorigenic pathways, such as epithelial-to-mesenchymal transition (EMT), TGF-β signaling, and immune modulation. The transfection of CICs with miRNA mimics led to the downregulation of oncogenic EMT markers (CRKL, lncRNA SOX2-OT, JUNB, SMAD3) and TGF-β pathway, resulting in a significant reduction of the in vitro proliferation and the tumorigenicity and migration in a zebrafish xenograft model. Additionally, miRNA-15a enhanced the expression of antigen processing machinery and decreased the expression of immune checkpoints (PD-L1, PD-L2, CTLA-4) and immunosuppressive cytokines (IL-4). The co-culture of HLA-matched lymphocytes with CICs overexpressing the miRNA-15a, elicited robust tumor-specific immune responses, characterized by a shift toward central and effector memory T cell phenotypes and prevented their terminal differentiation and exhaustion. The combination of miRNA modulation with Indoleamine 2,3-dioxygenase blockade and immunomodulating agents further potentiated these effects. Conclusions Our study demonstrates that the modulation of miRNA-15a in CICs not only suppresses the tumorigenic properties but also enhances their visibility to the immune system by upregulating antigen presentation and reducing immunomodulatory molecules. These findings suggest that combining miRNA modulation with epigenetic or immunomodulatory agents holds significant promise for overcoming treatment resistance in CRC. Graphical Abstract